THE STRUCTURAL AND SEMANTIC DYNAMICS OF WORD FORMATION IN MODERN ENGLISH MORPHOLOGY - Ahtamova Umida, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article provides an in-depth linguistic investigation into the mechanisms of word formation within the English language. Word formation is a pivotal branch of morphology that dictates how the lexicon adapts to socio-cultural and technological shifts.  The  study  evaluates  primary  productive  processes,  such  as  affixation, compounding,  conversion,  and  various  shortening  methods  including  blending  and clipping. By analyzing the structural and semantic shifts involved in these processes, the  research  highlights  how  English  maintains  its  status  as  a  highly  flexible  and expansive global tongue.